The effect of iodo alkyl chain transfer agents on the seeded emulsion homo- and co-polimerisation of styrene and butyl acrylate - Beyers, Cornelis Petrus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- Stellenbosch University, 1999.